Improving reproductive health self-efficacy among female adolescents through audiovisual based education: A pre-experimental study - Alim Hidayat; Eko Mardiyaningsih (Lentera Perawat, 2026)
Background: Adolescent girls need reproductive health education that not only provides accurate information but also strengthens confidence in making healthy decisions. School-based audiovisual education may offer an engaging and developmentally appropriate strategy to improve reproductive health self-efficacy among junior high school female. Objective: This study aimed to examine differences in self-efficacy among female adolescents before and after receiving PERSADA, an audiovisual-based reproductive health education intervention. Methods: This quantitative study used a pre-experimental one group pretest posttest design. A total of 161 female students from grades VIII and IX at a junior high school located in the Semarang regency were selected through purposive sampling from a population of 269 students. Self-efficacy was measured using a questionnaire administered before and after the intervention. Data were analyzed using descriptive statistics and the paired sample t-test. Results: The mean self-efficacy score increased from 61.37 before the intervention to 67.32 after the intervention, with a mean difference of 5.95 points. The minimum score increased from 48 to 56, while the maximum score increased from 76 to 79. The standard deviation decreased from 7.921 to 5.664, indicating more homogeneous post intervention scores. The paired sample t-test showed p = 0.000, indicating a statistically significant difference in self-efficacy before and after PERSADA. Conclusion: PERSADA was associated with a significant improvement in reproductive health self-efficacy among female adolescents These findings suggest that audiovisual-based reproductive health education can be used as a practical school-based health promotion strategy to strengthen adolescents’ confidence in understanding and maintaining reproductive health.